Analysis of Attractions, Amenities, and Accessibility as Competitiveness Factors of Umbul Sidomukti Semarang Tourist Destination Based on Google Reviews - Herman Novry Kristiansen Paninggiran; Dinar Anggit Wicaksana (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze tourist perceptions of the aspects of attraction, amenities, and accessibility at the Umbul Sidomukti tourist destination in Semarang, based on Google reviews from 2020 to 2023. A descriptive qualitative method was used, employing thematic analysis applied to 150 purposively selected reviews. The findings highlight that the most positive feedback was related to the attractions, particularly the natural panoramas, cool atmosphere, and adventure rides. Tourists appreciated the scenic beauty of the location and the opportunities for outdoor activities, which contributed to a satisfying experience at the destination. However, amenities such as toilet facilities, parking areas, and food stalls received more neutral to negative responses. Tourists expressed dissatisfaction with the cleanliness and maintenance of toilets, as well as the limited options for food stalls. These issues were seen as barriers to providing a complete and comfortable experience for visitors. Furthermore, accessibility emerged as the most critically assessed aspect, with numerous complaints about narrow, steep roads that were difficult for vehicles to navigate. Additionally, the lack of clear and sufficient directional signage was frequently mentioned, which made it challenging for tourists to find the location. The findings of this study reinforce the 3A-based destination development concept (Attraction, Amenity, Accessibility), emphasizing the need for a balanced approach in destination development. The core appeal of a destination, such as its attractions, must be complemented by well-developed supporting facilities (amenities) and ease of access. Based on these findings, the study offers strategic recommendations for local authorities and destination managers to focus on improving amenities and accessibility. By addressing these areas, it is expected that the overall tourist experience will be enhanced, leading to greater satisfaction and potentially increased visitor numbers to Umbul Sidomukti.